Relevansi Nilai Informasi Akuntansi : Studi Kasus Pada Saham Indeks LQ45 tahun 2021-2022 di BEI - Maulidayana, Rahmi; Nursaah, Aah; Uzliawati, Lia (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to examine the relevance of the value of accounting information including the relevance of earnings (EPS), the relevance of book value (BVEPS), the relevance of Return on Equity (ROE), and the relevance of the profit ratio from operational activities (NPM) simultaneously and partially using the stock price index model. LQ45 2021-2022 on the Indonesian Stock Exchange. The relevance of the value of this accounting information will later influence investors' decisions in choosing and investing their funds, especially in LQ45 shares. Sample selection used a purposive sampling technique which resulted in 82 samples. The test uses a multiple linear regression model with IBM SPSS Statistics 26 and the test results show that partially/individually, EPS and BVEPS accounting information has value relevance because it has a significant and positive effect on stock prices, but ROE and NPM information does not have value relevance because it does not have a significant effect. to share prices. Simultaneously / together, EPS, BVEPS, ROE and NPM information has an influence of 87.9% on share prices. Meanwhile, 12.1% were influenced by variables outside this research. BVEPS information has the most dominant influence on share prices in companies listed in the 2021-2022 LQ45 index on the Indonesian Stock Exchange.